EPC Agenda 2004-04-22 - Academic Senate:::::::::
Educational Policies Committee. Chair Report. Agenda – Approved. Minutes of 11/21/19 – Approved. Consent item: From EPC: Revision to Global Studies BA – Approved. President Report. Provost Report. Vice Chair Report. Vice President of Administration and Finance Report. Vice President for Student Affairs Report. Associated Students Report. Statewide Senators Report. Staff Representative Report. From EPC: Discontinuance of Reading and Language Arts Specialist Credential – Second Reading – Approved. From APARC: New Course Modules – Second Reading – Approved. Special Presentation: CSU/Elsevier Negotiations. EPC Report. FSAC Report. CFA Report.